Las nieblas en la Depresión del Ebro: el caso del Campo de Zaragoza y la Hoya de Huesca - Hernández Navarro, María Luz; Del Valle Melendo, Javier (Geographicalia, 2017)
This work analyses the fog-activity in two separated districts of the Ebro riverbasin: The Campo de Zaragoza area, located in its central sector and the Hoya de Huesca area, in a more marginal position and at a higher altitudinal level. Firstly a statistical-probabilistic study is made, followed by an analysis of the types of weather that lead to the apparition of this meteor.